2022
DOI: 10.3389/fchem.2022.873462
|View full text |Cite
|
Sign up to set email alerts
|

The Dopamine Assisted Synthesis of MoO3/Carbon Electrodes With Enhanced Capacitance in Aqueous Electrolyte

Abstract: A capacitance increase phenomenon is observed for MoO3 electrodes synthesized via a sol-gel process in the presence of dopamine hydrochloride (Dopa HCl) as compared to α-MoO3 electrodes in 5M ZnCl2 aqueous electrolyte. The synthesis approach is based on a hydrogen peroxide-initiated sol-gel reaction to which the Dopa HCl is added. The powder precursor (Dopa)xMoOy, is isolated from the metastable gel using freeze-drying. Hydrothermal treatment (HT) of the precursor results in the formation of MoO3 accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…This precursor was hydrothermally treated in 12 mL of water at 220 °C for 24 h. The product of the hydrothermal treatment was filtered and washed with copious amount of water. [41,42] Synthesis of Ti 3 AlC 2 MAX phase, Ti 3 C 2 MXene, and its free-standing film: Ti (99.5%, −325 mesh, Alfa Aesar), Al (99.5%, −325 mesh, Alfa Aesar), and TiC (99.5%, 2 μm, Alfa Aesar) powders were used for MAX phase synthesis. Lithium chloride (LiCl, 99%, Acros Organics), hydrofluoric acid (HF, 48.5-51%, Acros Organics), and hydrochloric acid (HCl, 36.5-38%, Fisher Chemical) were used for the synthesis and delamination of Ti 3 C 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This precursor was hydrothermally treated in 12 mL of water at 220 °C for 24 h. The product of the hydrothermal treatment was filtered and washed with copious amount of water. [41,42] Synthesis of Ti 3 AlC 2 MAX phase, Ti 3 C 2 MXene, and its free-standing film: Ti (99.5%, −325 mesh, Alfa Aesar), Al (99.5%, −325 mesh, Alfa Aesar), and TiC (99.5%, 2 μm, Alfa Aesar) powders were used for MAX phase synthesis. Lithium chloride (LiCl, 99%, Acros Organics), hydrofluoric acid (HF, 48.5-51%, Acros Organics), and hydrochloric acid (HCl, 36.5-38%, Fisher Chemical) were used for the synthesis and delamination of Ti 3 C 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This precursor was hydrothermally treated in 12 mL of water at 220 °C for 24 h. The product of the hydrothermal treatment was filtered and washed with copious amount of water. [ 41,42 ]…”
Section: Methodsmentioning
confidence: 99%
“…Comparison of these studies 8,12–16 reveals variations in structural properties of the resulting TMO/C materials, especially in terms of nanocomposite microstructure ( i.e. , phase distribution), degree of TMO reduction, and carbon hybridization.…”
Section: Introductionmentioning
confidence: 99%
“…8,11 Recent works have shown that the carbonization of amine molecules added into the interlayer of layered TMOs can produce TMO/C nanocomposites with a welldispersed carbon phase. 8,[12][13][14][15][16] In some cases, it was described that this synthesis route (and similar ones using different sources of carbon 17 ) yielded heterostructured TMO/C 12,16 (and transition metal dichalcogenide/carbon 18 ) nanocomposites, where layers of dissimilar phases alternate. This particular microstructure results in abundant heterointerfaces which may synergistically combine benecial electrochemical properties of the individual building blocks (redox-activity, electrical conductivity).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation